Early Iron Age economies - Lemos, IS (Cambridge University Press, 2022)
The centuries after the so-called collapse of the Mycenaean palace administration from the twelfth to the eighth centuries BCE saw several transformations of social and economic structures. These had an impact on the economic performance in the period. It is also significant that during this period there was no attempt to restore palatial administration, but instead Early Iron Age communities built new social and economic relationships on household units that could be understood as adaptable social-political organisations with fluid boundaries. Moreover, the Early Iron Age should not be seen as a period of stagnation but one characterised by adaptive and resilient features. These led to the well-documented visibility of the archaeological record of the eighth century BCE.